Informed Consent sebagai Upaya Perlindungan Hukum bagi Tenaga Kesehatan dalam Kasus Medis Darurat: Studi Kasus di Rumah Sakit Umum Daerah Provinsi Papua Barat - Winarti Winarti; Rizka Rizka (LPPM Universitas 17 Agustus 1945 Semarang, 2024)
This study aims to analyse informed consent, legal protection and health workers in the Regional General Hospital of West Papua Province. The research method used is a quantitative approach. The data analysis used was descriptive analysis and verification analysis using multiple linear regression analysis. The descriptive method focuses on describing and analysing the research results and the verification method is used to test the relationship between variables. The sample consisted of 35 respondents who were taken using saturated sampling technique. The results of descriptive analysis showed that in the variables of informed consent, legal protection, and health workers were in the category of very unaware of the insights of health workers in the application of informed consent in emergency medical cases, and there were still some shortcomings that must be considered to be corrected. The results of this study indicate that statistically the results of verification tests with multiple linear regression analysis models show that the informed consent variable has a significant effect on health workers with a coefficient value of 0.542 and a p-value of 0.044. Legal protection also has a significant effect on health workers with a coefficient value of 1.755 and a p-value of 0.000. Meanwhile, informed consent, legal protection showed a significant effect simultaneously on health workers with an F value of 14,079 and a p-value of 0.000.